Human Milk Oligosaccharides as Promising Antivirals. Issue 6 (1st March 2018) - Morozov, Vasily; Hansman, Grant; Hanisch, Franz‐Georg; Schroten, Horst; Kunz, Clemens
Abstract: Human milk oligosaccharides (HMOs) are diverse unconjugated carbohydrates that are highly abundant in human breast milk. These glycans are investigated in the context of exhibiting multiple functions in infant growth and development. They seem to provide protection against infectious diseases, including a number of poorly manageable viral infections. Although the potential mechanism of the HMO antiviral protection is rather broad, much of the current experimental work has focused on studying of HMO antiadhesive properties. HMOs may mimic structures of viral receptors and block adherence to target cells, thus preventing infection. Still, the potential of HMOs as a source for new antiviral drugs is relatively unexploited. This can be partly attributed to the extreme complexity of the virus‐carbohydrate interactions and technical difficulties in HMO isolation, characterization, and manufacturing procedures. Fortunately, we are currently entering a period of major technological advances that have enabled deeper insights into carbohydrate mediated viral entry, rational selection of HMOs as anti‐entry inhibitors, and even evaluation of individual synthetic HMO structures. Here, we provide an up‐to‐date review on glycan binding studies for rotaviruses, noroviruses, influenza viruses, and human immunodeficiency viruses. We also discuss the preventive and therapeutic potential of HMOs as anti‐entry inhibitors and address challenges on the route from fundamental studies to clinical trials. Abstract : An up‐to‐date review on glycan binding studies (histo‐blood group antigens, human milk oligosaccharides) for human immunodeficiency viruses, rotaviruses, noroviruses, and influenza viruses is given. The preventive and therapeutic potential of HMOs as anti‐entry inhibitors and challenges en route from fundamental studies to clinical trials will be addressed.